Looking beyond a temple: Archaeological diagnosis at Banteay Srei, Cambodia, 2007/08 - Arndt, Robert C.; Hoffmann, Simon; Buess, Manuel; Gerber, Bruno; Sonnemann, Till (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
A diagnostic archaeological campaign investigated a larger area east of the Angkorian temple of Banteay Srei (Cambodia) in 2007/08. Various geophysical techniques were combined with the excavation of long cross-sections to provide a comprehensive image of the archaeological remains. A newly documented unexcavated sandstone building apparently belongs to the sanctuary nearby. A paved axial access road could be detected almost 300 m east of the temple entrance. Various trenches and basins once characterised the landscape, while there were only few indications of buildings. While the campaign was initiated by the Swiss-Cambodian Banteay Srei Conservation Project to prepare the reorganization of the site and the construction of a new museum, it has yielded a lot of information on the use of the area close to a rural centre in the Angkorian kingdom.The article will be available as a PDF in the near future.